Research on Enryo Hojo, Core Member of Unit 731 and Bacteriological Warfare - Wenjing GONG; Pengying LI (Yixue yu zhexue)
After World War Ⅱ, in order to avoid war crimes prosecution, the Unit 731 members handed over their research materials to the United States. Enryo Hojo, a figure who left a dark mark in the history of Japanese biological warfare, has largely remained outside the academic spotlight due to a lack of historical sources. This article systematically reviews Enryo Hojo's medical and military career, using research reports written by him, which are preserved in both the United States and Japan, as a guide. It explores the multifaceted roles of Unit 731's medical personnel within the wartime military-academic collaboration system and provides detailed accounts of the biological warfare experiments and tactics employed by Unit 731. These research reports are not only important materials for biological warfare studies but also serve as necessary references for examining Japanese colonial medicine during World War Ⅱ and as critical evidence revealing the medical crimes committed by Unit 731.